Small Cages with Insect Couples Provide a Simple Method for a Preliminary Assessment of Mating Disruption - Françoise Briand; Patrick M. Guerin; Pierre-Joseph Charmillot; Patrik Kehrli (The Scientific World Journal)
Mating disruption by sex pheromones is a sustainable, effective and widely used pest management scheme. A drawback of this technique is its challenging assessment of effectiveness in the field (e.g., spatial scale, pest density). The aim of this work was to facilitate the evaluation of field-deployed pheromone dispensers. We tested the suitability of small insect field cages for a pre-evaluation of the impact of sex pheromones on mating using the grape moths Eupoecilia ambiguella and Lobesia botrana, two major pests in vineyards. Cages consisted of a cubic metal frame of 35 cm sides, which was covered with a mosquito net of 1500 μm mesh size. Cages were installed in the centre of pheromone-treated and untreated vineyards. In several trials, 1 to 20 couples of grape moths per cage were released for one to three nights. The proportion of mated females was between 15 to 70% lower in pheromone-treated compared to untreated vineyards. Overall, the exposure of eight couples for one night was adequate for comparing different control schemes. Small cages may therefore provide a fast and cheap method to compare the effectiveness of pheromone dispensers under standardised semi-field conditions and may help predict the value of setting-up large-scale field trials.